PENDIDIKAN PASTORAL KONSELING DALAM GEREJA YANG RESPONSIF TERHADAP KESEHATAN MENTAL JEMAAT - Meidy Sumeleh; Patricia Gagola; Militia Christy Saranaung; Francien Angraini Hutri Lintjewas (PT. Giat Konseling Nusantara, 2025)
Abstract Mental health plays a crucial role in every individual's life, enabling them to utilize their cognitive and emotional abilities optimally throughout daily activities while fulfilling their needs. However, attention towards mental health often falls short, particularly in developing countries where this issue is considered less urgent compared to infectious diseases. Research has shown that there exists a correlation between physical and mental well-being, with individuals experiencing physical issues frequently exhibiting signs of psychological disturbances. Conversely, those suffering from mental disorders commonly experience decreased physical function. When someone faces mental health challenges, they tend to feel isolated and struggle forming connections with others. Lack of social support coupled with deep loneliness can exacerbate mental conditions further, even increasing suicidal tendencies. In the context of churches, pastoral counseling becomes essential in supporting congregants dealing with mental health issues. Through educational pastoral counseling programs, church leaders can provide comprehensive support encompassing spiritual, emotional, and psychological aspects while reducing associated stigma. This study employs qualitative research methods using descriptive approaches to outline the roles and strategies involved in implementing responsive pastoral counseling services within churches addressing members' mental health concerns. Findings indicate that churches can serve as supportive environments offering hope and assistance during an individual’s recovery process from mental health afflictions.